The biotechnology for rearing of juvenile Baltic salmon on the artificial food mixture KRT - Kotova, N.I.; Malikova, E.M.; Reznikova, N.S. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva; "Zvaigzne", 1968)
Methods of mass rearing of young salmon (Salmo salar) in Latvia are described. Recommendations on the collection and incubation of eggs, on the maintenance and rearing of larvae are presented. Rearing of the young stages of salmon after the transition of larvae to the active feeding, during their wintering and the period up to the smoltification was described. A broad introduction of the feeding mixture KRT is suggested, allowing an increase in the efficiency of fish hatcheries. Published Not Known